The Monetary Policy Credibility Channel and the Amplification Effects in a Semi-structural Model - Chansriniyom, Thitipat (IMF Working Papers; Working Paper ;, 2020)
The paper extends a standard semi-structural model to account for nonlinear and asymmetric effects of monetary policy credibility. In our setting, central bank credibility is proportional to the deviation of inflation expectations from the announced inflation target, with positive deviations being more costly compared to negative ones. A loss in policy credibility as a result of shocks leads to a more persistent, backward-looking inflation process, and is associated with lower output. We find that the extended model with credibility effects matches well the key macroeconomic data over specific past episodes for Indonesia and Philippines and consider its adaptation to integrated policy frameworks as an area for further exploration.